Casing vibration response prediction of dual-rotor-blade-casing system with blade-casing rubbing. (1st March 2019) - Wang, Nanfei; Liu, Chao; Jiang, Dongxiang; Behdinan, Kamran
Highlights: Based on the actual structure of aero-engine, the FE model of a dual-rotor-blade-casing (DRBC) system is developed. The vibration responses of inner rotor and casing under blade-casing rubbing are compared, and the dynamic characteristics are extracted. The effects of the rotating speed ratio, eccentricity of disk and rubbing stiffness on the dynamic behaviors are investigated in detail. Abstract: This paper focuses on the dynamic responses of whole aero-engine with blade-casing rubbing. The vibration response of casing is simulated and the dynamic behaviors of casing acceleration under blade-casing rubbing are investigated to diagnose the blade-casing rubbing fault effectively. Firstly, the finite element model of a dual-rotor-blade-casing (DRBC) system with inter-shaft bearing is proposed. The shear deformations and inertias of the rotor and casing are taken into account. The gyroscopic moments of the rotors are evaluated. Secondly, the effects of the blade-casing clearance and the number of blades on the vibration responses of DRBC system with blade-casing rubbing are considered. Finally, the casing acceleration responses of the DRBC system with blade-casing faults are solved numerically, and the influences of some variables, such as the rotating speed ratio, eccentricity of disk and rubbing stiffness, on the dynamic behaviors have been investigated by time waveform of acceleration, frequency spectrum and waterfall. The results indicate that (1) blade-casing rubbing can cause impulsive load to the casing and rotor, and lead to abrupt increase of the vibration amplitude; (2) the obvious periodic impact characteristics are contained in the casing vibration acceleration signals, and the impact frequency equals the product of the rotational frequency and the numbers of blades; (3) the fraction frequency component of rotating speed difference of dual rotors is excited on both sides of impact frequency and its multiple frequency components.